Jet-cloud interactions in the BLR of Centaurus A - Araudo, Anabella Teresa (2009)
Active galactic nuclei present continuum and line emission. Some of these lines are broad, and would be produced by clouds located in a region close to the central black hole. Centaurus A is the nearest active galactic nuclei and it has an obscured nucleus likely harboring clouds. In this work, we study the interaction of these clouds with the jet and compute the produced non-thermal emission. The resulting radiation may be detectable.